Comparison of regional citrate anticoagulation and nafamostat mesylate anticoagulation during plasma exchange for children at high bleeding risk: a retrospective study - Dan Peng; Zili Cai; Jie He; Wei Duan; Xinping Zhang (Italian Journal of Pediatrics)
Abstract Background There is currently no established optimal anticoagulation protocol for plasma exchange (PE) in pediatric patients at a high risk of bleeding. Therefore, we aimed to evaluate the efficacy and safety of regional citrate anticoagulation (RCA) and nafamostat mesylate (NM) for PE anticoagulation in this patient group. Methods This retrospective study analyzed data from 66 children with high bleeding risk who underwent PE in the Pediatric Intensive Care Unit of Hunan Children’s Hospital between June 2018 and January 2023. Patients were divided into two groups: RCA-PE (n = 45) and NM-PE (n = 21), and filter performance and adverse reaction rates were compared. Statistical analysis utilized SPSS 25.0, comprising two-sample t-tests, chi-square or Fisher’s exact tests, and Mann–Whitney U tests, as appropriate. Data visualization was performed using ggplot2 in R-studio. P < 0.05 was considered statistically significant. Results No statistically significant differences were found between the two groups in initial transmembrane pressure (TMP) [17.0 (14.0, 21.5) mmHg vs. 16.0 (14.0, 19.5) mmHg, P = 0.614], maximum TMP [46.0 (42.0, 49.5) mmHg vs. 43.0 (41.5, 49.5) mmHg, P = 0.689], and final TMP [40.0 (35.5, 45.0) mmHg vs. 38.0 (35.0, 42.0) mmHg, P = 0.298]. Filter grade distribution and bleeding events also showed no statistically significant difference between the groups. However, the NM-PE group had significantly lower overall adverse reaction and metabolic alkalosis rates (both P < 0.05) compared to the RCA-PE group. Conclusions NM demonstrates similar efficacy but superior safety compared with RCA, making it a more suitable anticoagulation strategy for children with high bleeding risk. Study limitations include single-center design, selection bias, and uncertain NM dosage.